Cost-benefit analysis of performance based budgeting implementation - Trenovski, Borce; Nikolov, Marjan (Center for Economic Analyses, 2015)
This is the first study which estimates costs and benefits of overall policy reform for implementation of performance based budgeting. Costs estimation is based on a phased implementation, where we consult the Regulatory Impact Assessment methodology. In order to estimate benefits, we use a microeconomic approach to assess technical efficiency (Data Envelopment Analysis-DEA and Stochastic Frontier Analysis-SFA) of the budget users. The estimated benefits are higher than the estimated costs, or for every Macedonian denar invested in this reform an additional 2,600-8,000 Macedonian denars of gross value added in the Macedonian GDP are expected.
Keywords: performance based budgeting, cost–benefit analysis, budget systems, public finance, technical efficiency, Macedonia